PENGEMBANGAN ALAT BANTU LATIHAN UNTUK PROSES REHABILITASI BAGI PASIEN PASCA STROKE - Titiek Koesdijati; M. Nushron Ali M (LPPM Universitas PGRI Adi Buana Surabaya, 2017)
Stroke is a disease that is still considered terrible at this time, the cause is none other than due to lifestyle and unhealthy diet. It is this condition that causes post-stroke patients can not freelyengage, therefore a therapeutic device design is needed so that patients can be cured of paralysisimmediately. The design process using QFD method so that the needs and designs are expected tobe in accordance with the wishes of the patient. Anthropometry is used to determine the size of thepatient's palm. The eco design method is used in the selection of materials to be used to support thecreation of green production. The results of anthropometric data measurement for the 5th percentileare at Ptm = 73.26mm, Dgmak = 20.85mm, Ttm = 16.98, while for the 95th percentile in the Ltm =92.32, Dgmin = 14.09, Lkt = 102.78 and Tgkt = 63.93. Test data reliability shows that theadjustability aspect has the highest value of 0.9156, then ranks both finishing aspects with the valueof 0.867 and the last is the material aspect with the value 0.7562. Based on the overall attributeused as instrumentation, which is a number of 13 attributes. The highest rating is on the easyattribute in the assembly.